THE IMPROVEMENT OF PREDICTION SKILLS AND CONCEPT’S MASTERY ON LEARNING CYCLE THREE-PHASE - julia woro andrian; nina kadaritna; noor fadiawati (Universitas Lampung, 2013)
This research aimed to describe the Learning Cycle three-phase (LC 3E) learning model that are effective in improving the prediction skills and concept’ mastery on acid-base material. The sampling technique used purposive sampling technique. This research use a quasi-experimental methods with Non Equivalent (Pretest and Posttest) Control Group Design. The sample in this research is students of State Senior High School 1 Pekalongan in East Lampung and obtained XI sains 1 and XI sains 4 class at school year 2013-2014 which has almost the same characteristics. The effectiveness of LC 3E learning model measured on the difference and the improvement of a significant gain. The results showed the average value of n-Gain prediction skills for control class and experiment class are 0.37 and 0.62, and the average value of n-Gain concept’ mastery for control class and experiment class are 0.53 and 0.65. Based on the test of the hypothesis, it is known that a class with LC 3E learning model has prediction skills and concept’ mastery higher than conventional class learning. This showed that the LC 3E learning was more effective in improving the prediction skills and concept’s mastery.Keywords: Learning Cycle three-phase, the prediction skills, and concept’ mastery.